2020
DOI: 10.1021/acs.langmuir.0c01849
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Reduction–Adsorption Strategy for Cr(VI): Fabrication and Application of L-Cysteine-doped Carbon@Polypyrrole with a Core/Shell Composite Structure

Abstract: Reclamation and recycling of heavy metal ions can offer environmental protection and sustainable development. Here, we report the preparation of L-cysteine (L-cys)-doped glucose carbon sphere (GCS)@polypyrrole (PPy) composites (GCS@PPy/L-cys). The adsorption performance and mechanism of GCS@PPy/L-cys toward Cr­(VI) from water were investigated in detail. The chromate enrichment on GCS@PPy is significantly facilitated by doping with L-cys, which prevents the oxidative collapse of the structure. This approach le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 51 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…It has large specific surface area for adsorption but commercial AC is typically expensive hence cheaper and renewable agricultural raw material have been utilised for the fabrication of AC and biochar. Due to the outstanding adsorption properties (Ghosh et al 2020) they can be used in PPy doping to produce Cr(VI) ions exceptional adsorbents and several studies have been reported to this end (Thamilarasu et al 2012;Wang et al 2013;Omwoyo et al 2015;Chen et al 2020;Li et al 2020;Reis et al 2021). Furthermore, dispersed graphene oxide (GO), is capable of providing highly active PPy-based nanocomposite with remarkable Cr(VI) ions removal efficiency (Setshedi et al 2015).…”
Section: Polypyrrole Modified Carbon Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has large specific surface area for adsorption but commercial AC is typically expensive hence cheaper and renewable agricultural raw material have been utilised for the fabrication of AC and biochar. Due to the outstanding adsorption properties (Ghosh et al 2020) they can be used in PPy doping to produce Cr(VI) ions exceptional adsorbents and several studies have been reported to this end (Thamilarasu et al 2012;Wang et al 2013;Omwoyo et al 2015;Chen et al 2020;Li et al 2020;Reis et al 2021). Furthermore, dispersed graphene oxide (GO), is capable of providing highly active PPy-based nanocomposite with remarkable Cr(VI) ions removal efficiency (Setshedi et al 2015).…”
Section: Polypyrrole Modified Carbon Materialsmentioning
confidence: 99%
“…Overally, the adsorption mechanisms of PPy-based adsorbents appeared to have taken place by the reduction of Cr(VI) species to Cr(III) species under acidic conditions. In the meantime, the amine group (ÀNHÀ) of PPy is partially oxidised to the positively charged species (-NH•þ) which can attract Cr(VI) ions (Li et al 2020). Thus, the adsorption process was associated with ion exchange, electrostatic attractions, complexation, chelation reactions with protonated sites and reduction (Tran et al 2019;Liu et al 2021;Mdlalose et al 2021).…”
Section: Regeneration Of Ppy-based Adsorbentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, cysteine is also known as L-cysteine. Safe and non-toxic can effectively reduce the secondary pollution to the environment during water treatment [19].…”
Section: Introductionmentioning
confidence: 99%